Becoming a Resilient Mother: The Impact of Breastfeeding Self-Efficacy and Multiparity on Emotional Adjustment of Postpartum Mothers - Julia Fitrianingsih; Dian Meiliani Yulis; Sriyana Herman; Fitriani Fitriani (Public Health of Indonesia, 2026)
Background: The postpartum period is a critical phase characterized by significant emotional and psychological transformations Objective: This study aims to investigate the effect of breastfeeding self-efficacy and multiparity on the emotional adjustment of postpartum mothers Method: The research design used was a cross-sectional study to collect data from 101 Breastfeeding mothers. The sample consisted of all postpartum mothers who gave breastmilk. The inclusion criteria were gestational age of at least in women with a singleton pregnancy, 34 weeks, no breast abnormalities, and no smoking or alcohol consumption. Mothers and infants who need special care were excluded. The BSE Scale-Short Form questionnaire was used to collect data. This used crosstabulation, chi-square testing, and regression to evaluate the data to clearly and formally describe the statistical analyses performed. Results: The results showed that mothers with high BSE were much more likely to say they were emotionally stable, with an odds ratio (OR) of 12.54 (p <.001), which means there was a strong connection between BSE and emotional adjustment through multiparity. The crosstab analysis showed that multiparity was likewise statistically significant (p = .000), but when BSE was controlled, regression showed that its effect was not significant (p = .558). Conclusion: The study concludes that breastfeeding self-efficacy is more important than multiparity in determining how well a mother adjusts emotionally after giving birth. Interventions that build BSE may help new mothers feel better emotionally.  Keywords: Breastfeeding Self-Efficacy; Emotional Adjustment; multiparity; postpartum